How to enhance effectiveness of direct attack judo throws - Sacripanti, A. (arXiv e-print repository, 2014)
In this paper is performed an appraisal of the Olympic Sport Judo effectiveness in the optics of Biomechanics. To broaden the classical view,the field of experimentation is obviously the high level competition in which most of rotational application can be found applied more or less instinctively by high level Athletes. Considering the two biomechanical tools that are the physical basis of judo throws it is possible to obtain such results from the analysis of high competition application: Lever Techniques are enhanced in their effectiveness in three ways: The rotational movements, strictly connected to the Lever techniques mechanics achieving victory in competition, can be extended to the unbalance phase. The rotational movements can be applied in a totally new way putting away even the unbalance that is basic in the Lever techniques. The Lever tool can be hybridized with the Couple tool to lower the energy consumption. Couple Techniques are enhanced in their effectiveness also in three ways: The Couple tool that doesnt need unbalance allowing uke body rotate around his center of mass, is enhanced utilizing the Uke body smaller resistance directions,normally summarized in Diagonal attacks. The vertical rotational movements in the transverse plan with the axis in the sagittal plane can be added to the Couple application with transverse rotation and axis in the frontal plane to overcome some defensive resistance, mainly in the trunk and leg group of Couple techniques, like Uchi Mata or O Soto Gari. The rotational movements enhance the throwing action changing the mechanics of Couple into Lever applying a Torque,both with the direction change of one force or the time delay of his application. This analysis, expanded with a short physical framework, clarifies hidden deep concepts and helps teacher and coaches in their professional work. ( this paper will be published,in Italian language, without mathematical framework into the Italian Judo Federation Magazine: "Athlon" FIJLKAM Yr 2014 )